Thermal behaviors and flow profiles in a square channel fitted with XV modified ribs: A numerical analysis - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2023)
A novel design of "X–V rib" turbulators is proposed to improve fluid blending and to perturb thermal boundary layer (TBL) in a heat exchanger (HX) duct. Better fluid blending and more highly disturbed TBL are the two important factors for the improvement of HX performance. Effects of X–V rib geometrical parameters including rib height ratios (b/H = 0.05–0.20), rib arrangements (V-tip pointing upstream called "V-Upstream (VU)" and V-tip pointing downstream called "V-Downstream (VD)") and rib types (I, II and III) on air stream and thermal mechanisms are numerically investigated in a 3D model. The numerical model is solved with the finite volume method (a commercial code) and a commercial program. Laminar air flow (inlet conditions with Re = 100–2000) is a selected range of the present investigation. Firstly, the created numerical model for the ribbed duct is validated with two significant topics: 1. Plain duct validation and 2. Optimum grid elements (grid independence). The validated results show that the ribbed-duct model has great reliability to simulate air stream and thermal characteristics. According to the numerical results, the disturbed TBL is obviously found in all rib types. Moreover, it is observed that the core flow disturbance occurs and improves fluid blending. The outcomes from the present investigation point out that the knowledge about flow structure and thermal mechanism are important guidelines for the development of vortex turbulators and HX improvement. For the thermal assessments, it is found that the best Nusselt number ratio (Nu/Nu0) is 11.80 for the type III X–V rib with b/H = 0.20 in the VD-direction. Additionally, the maximum thermal enhancement factor within our investigated range is 3.48 at Re = 2000, b/H = 0.20, type II X–V rib in the VU-direction.
Keywords: Turbulator; Heat Transfer Mechanisms